puffandclim
puffandclim
01-02-2018
Mathematics
contestada
Solve for y: 2(3y-4)=3(y-2/3)
Respuesta :
raulnhurtado
raulnhurtado
01-02-2018
2*(3*y-4) = 3*(y-(2/3)) // - 3*(y-(2/3))
2*(3*y-4)-(3*(y-(2/3))) = 0
2*(3*y-4)-3*(y-2/3) = 0
2*(3*y-4)-3*(y-2/3) = 0
3*y-6 = 0
3*y-6 = 0
3*y-6 = 0 // + 6
3*y = 6 // : 3
y = 6/3
y = 2
y = 2
Answer Link
VER TODAS LAS RESPUESTAS ( 73+ )
ACCESS MORE
Otras preguntas
If selecting samples of size n > 30 from a population with a known mean and standard deviation, what requirement, if any, must be satisfied in order to assum
Solve tan(3x)=1 if -pi≤x≤pi.
amal distributed 12 more questionnaires than Pat. Eli distributed 15 fewer questionnaires than Pat. Martine distributed the same number of questionnaires as A
How does the structure of the skeletal muscle help it perform its function?
Write a possible explicit rule for the nth term of the sequence: 1, 1/2, 1/3, 1/4, 1/5, ... A.an = 1/n-1 B.an = 1/an-1 C.an = 1/n2 D.an = 1/n
28 men can finish the job in 60 days. At the start of the 16 day, 5 men were laid off and after the 45th, 10 more men were hired. How many days were delayed in
If a matrix is not invertible, can I say the matrix has many solutions? Or is the matrix has many solutions as well as the possibility or no solutions? And so i
Which of the following choices states a difference between dialogue and formal speech? A. Dialogue is more likely to contain sentence fragments. B. Dialog
What's the boiling point and Melting point for calcium?
For all x > 0 and y > 0, the radical expression: √x divided by 3√x-√y is equivalent to. 3x + √xy divided by 9x-y. SOLVE.